2017
DOI: 10.1039/c7ra10556h
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of EuPO4 nano/microstructures and core–shell SiO2@EuPO4 nanostructures with improved photoluminescence

Abstract: Cluster-like, flower-like and sphere-like EuPO 4 nano/microstructures and uniform core-shell SiO 2 @EuPO 4 nanostructures have been controllably synthesized by the hydrothermal route and co-precipitation method, respectively. The as-synthesized products are characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS) and infrared spectroscopy (IR). The possible formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Also, the PL intensity of the magnetic‐dipole transition of 5 D 0 – 7 F 1 is stronger than that of the electronic‐dipole transition of 5 D 0 – 7 F 2 . In addition, the same situation can be observed in hexagonal EuPO 4 ·H 2 O nanorods and nanowires, EuPO 4 nano/microstructures and core–shell SiO 2 @EuPO 4 nanostructures in the literature [17–21]. Moreover, Yan et al concluded that the dominant 5 D 0 − 7 F 1 emission for Eu 3+ ions in the hexagonal environment of LnPO 4 :Eu 3+ nanowires originated from a magnetic‐dipole transition [24].…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Also, the PL intensity of the magnetic‐dipole transition of 5 D 0 – 7 F 1 is stronger than that of the electronic‐dipole transition of 5 D 0 – 7 F 2 . In addition, the same situation can be observed in hexagonal EuPO 4 ·H 2 O nanorods and nanowires, EuPO 4 nano/microstructures and core–shell SiO 2 @EuPO 4 nanostructures in the literature [17–21]. Moreover, Yan et al concluded that the dominant 5 D 0 − 7 F 1 emission for Eu 3+ ions in the hexagonal environment of LnPO 4 :Eu 3+ nanowires originated from a magnetic‐dipole transition [24].…”
Section: Resultsmentioning
confidence: 64%
“…Phase transition temperature was observed at approximately 700°C [17]. Significant effort has been made to develop various monoclinic and hexagonal EuPO 4 nanostructures such as nanoparticles, nanorods, nanowires, and nanospheres, and their luminescent properties have been investigated [17][18][19][20][21]. However, there are no known reports about the fabrication of uniform and monodisperse EuPO 4 hollow spheres in the literature up to now.…”
Section: Introductionmentioning
confidence: 99%
“…When the size of the nanoparticles decreased, the ratio of Eu 3+ ions in the surface of nanoparticles would be increased. Therefore, the decrease of the symmetry around the Eu 3+ ions would lead to the enhancement of the 5 D 0 → 7 F 2 transition 32,36,37 . To further understand the f-f transition and the local symmetry properties of Eu 3+ ions in the LaPO 4 crystal lattice, the optical transition strength parameters (Ω 2 and Ω 4 ) were calculated by the well-known Judd-Ofelt (J-O) theory.
Figure 6Excitation spectra of the products: S1, S2 and S3.
Figure 7Emission spectra of the products: S1, S2 and S3.
…”
Section: Resultsmentioning
confidence: 99%
“…Xu et al have synthesized a luminescent and mesoporous core-shell structured Gd 2 O 3 :Eu 3+ @SiO 2 nanocomposite and make it as a drug carrier [19]. In our previous studies, we have synthesized SiO 2 @EuPO 4 by co-precipitation using triethyl phosphate [20]. It was found that the core-shell nanostructure can significantly improve the emission strength of the material.…”
Section: Introductionmentioning
confidence: 99%